Influence of Filler Dispersion on the Mechanical Properties of Nanocomposites. (2016) - Cosmoiu, Ioana; Apostol, Dragos A.; Picu, Catalin R.; Constantinescu, Dan M.; Sandu, Marin; Sorohan, Stefan
Abstract: Specific manufacturing technologies were applied for the fabrication of epoxy-based nanocomposites with multi-wall carbon nanotubes (MWNT) and nanoparticles (silica and alumina). For dispersing the fillers in the epoxy resin special equipment such as a shear mixer and a high energy sonicator with temperature control were used. The considered filling fractions were, in most cases, 0.1, 0.3 and 0.5 wt%. Usually, the dispersion process (mechanical mixing and sonication) cannot be completed successfully if the percentage is increased above 3 wt%. The nanocomposites were subjected to monotonic uniaxial testing using standardized traction specimens. Only an adequate dispersion of fillers may lead to an increase of strength and stiffness.